Nuclear receptors of NR1 and NR4 subfamilies in the regulation of microglial functions and pathology - Hiroshi Katsuki (Wiley, 2021)
Abstract This review provides an overview of researches on the NR1 and NR4 nuclear receptors involved in the regulation of microglial functions. Nuclear receptors are attractive candidates for drug targets in the therapies of the central nervous system disorders, because the activation of these receptors is expected to regulate the functions and the phenotypes of microglia, by controlling the expression of specific gene subsets and also by regulating the cellular signaling mechanisms in a nongenomic manner. Several members of NR1 nuclear receptor subfamily have been examined for their ability to regulate microglial functions. For example, stimulation of vitamin D receptor inhibits the production of pro‐inflammatory factors and increases the production of anti‐inflammatory cytokines. Similar regulatory actions of nuclear receptor ligands on inflammation‐related genes have also been reported for other NR1 members such as retinoic acid receptors, peroxisome proliferator‐activated receptors (PPARs), and liver X receptors (LXRs). In addition, stimulation of PPARγ and LXRs may also result in increased phagocytic activities of microglia. Consistent with these actions, the agonists at nuclear receptors of NR1 subfamily are shown to produce therapeutic effects on animal models of various neurological disorders such as experimental allergic encephalomyelitis, Alzheimer's disease, Parkinson's disease, and ischemic/hemorrhagic stroke. On the other hand, increasing lines of evidence suggest that the stimulation of NR4 subfamily members of nuclear receptors such as Nur77 and Nurr1 also regulates microglial functions and alleviates neuropathological events in several disease models. Further advancement of these research fields may prove novel therapeutic opportunities.